Mind the Gap: Gap Affordance Judgments of Children, Teens, and Adults in an Immersive Virtual Environment - Creem-Regehr, Sarah H.; Gill, Devin M.; Pointon, Grant D.; Bodenheimer, Bobby; Stefanucci, Jeanine K. (Frontiers in Robotics and AI, 2019)
Affordances are possibilities for action that depend on both an observer's capabilities and the properties of the environment. Immersive Virtual Environments (IVEs) have been used to examine affordances in adults, demonstrating that judgments about action capabilities are made similarly to the real world. However, less is known about affordance judgments in middle-aged children and adolescents in IVEs. Differences in rate of growth, decision criteria, and perceived risk could influence affordance judgments for children. In Experiment 1, children, teens, and adults stood in an IVE at ground level or at a height of 15 m, and were asked to view gaps of different widths. Across all age groups, estimates of gap crossing were underestimated at the higher height compared to the ground, consistent with reports of fear and risk of falling. Children, compared to adults, underestimated their maximum crossable gap compared to their actual crossable gap. To test whether this difference was specific to IVEs or a more generalized age effect, children and adults were tested on gap estimates in the real world in Experiment 2. This real world study showed no difference between children and adults, suggesting a unique contribution of the IVE to children's affordance judgments. We discuss the implications for using IVEs to study children's affordances.